The Effect of Self-Esteem on Resilience among Victims of Bullying: Does Gender Play a Role? - Saaduddin Saaduddin; Eko Sujadi; Nuzmi Sasferi; Desri Jumiarti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Bullying has become a serious issue in educational institutions. Bullying causes significant negative effects on physical, social, and psychological aspects. The purpose of this study is to investigate the influence of self-esteem on resilience. We also analyzed the resilience differences between male and female students. Through a cross-sectional study design, 86 students participated in completing a survey. The Multidimensional Peer-Victimization Scale developed by Mynard & Joseph was used to determine respondents who were victims of bullying. Furthermore, The Brief Resilience Scale (BRS) and Rosenberg Self-Esteem Scale (RSE) were used to measure resilience and self-esteem. The data analysis technique used to reveal the difference in resilience of bullying victims between males and females is the independent sample t-test. Furthermore, simple regression is used to test the influence of self-esteem on resilience. The results showed that students' self-esteem and resilience were moderate. There was a significant difference in resilience between male and female students, with males having higher resilience than females. Testing also proved that there is an influence of self-esteem on students' resilience. This study has implications for the importance of addressing bullying in schools. Furthermore, psychological interventions through counseling services can be implemented to improve resilience.